Voice and silence behaviors of university students in curricular internships - Marinho Costa, Fabíola (2023)
Introduction: Training for the professional practice of Psychology, as in other professions, requires, as a first approximation, the experience of internships, when situations that demand professional intervention are experienced by the student. Objective: to understand factors that motivate or inhibit the expression (voice) or retention (silence) of ideas, information, opinions or concerns related to the work developed in the curricular internship. Method: interviews were conducted with 15 Psychology students whose curricular internships were carried out in multidisciplinary teams. We sought to understand the meanings that the narrated experiences had for the interviewees. Results: both forces acting in the direction of speech and in the direction of remaining silent were identified, related to five factors: individual dispositions; attitudes and perceptions; emotions and beliefs; supervisor behavior; and contextual factors. Conclusion: the importance of developing practices in Psychology training that prioritize work in collective and interprofessional environments is highlighted.